(untitled) (Journal of actual problems of jurisprudence, 2018)
The article deals with legislative support through development of proposals for improving the criminal procedural, through the analysis of theoretical bases of Institute of the procedural agreement in the domestic proceedings. The article includes, the application the new code, the use of four types of punishment for the crime. In particular, confiscation of property, deprivation of a rank, a rank, awards, and restriction to engage in certain activities. It is known that all these penalties the current law is applied as the main punishment. The new Criminal code, failure to pay the penalty provided for the punishment of deprivation of liberty. In this case, one day in the colony is equal to the volume of penalty, that is, the four dimensions MCI. As well as a forward proof, the fact of deliberate non-payment of the fine is not necessary. This will have an impact to speed up the collection of the health, those who today refuse to pay fines. The article also provided for use in the educational process and scientific research on emerging issues related to standards and the system of criminal law and criminal process. Key words: сriminal proceedings, pre-trial investigation, criminal offence, criminal prosecution, investigation techniques.